Entrevista a Gary Born. El Arbitraje Internacional en debate - Narancio, Victoria; Núñez del Prado, Fabio (Pontificia Universidad Católica del Perú, 2017)
Is the choice of the arbitral seat still an important decision in international arbitration? Should arbitral awards be subject to greater judicial scrutiny? Should the appeal be in international arbitration? Is it possible that an annulled arbitral award is recognized under the New York Convention? Should the New York Convention be amended to achieve CNY 2.0? Is investment arbitration a system that works? Are the criticisms of investment arbitration valid? In this interview, Gary Born responds to each of these questions by addressing many controversial current issues in international arbitration.

¿Es la elección de la sede del arbitraje todavía una decisión importante en el arbitraje internacional? ¿Deberían los laudos estar sometidos a un mayor escrutinio judicial? ¿Debería existir la apelación en el arbitraje internacional? ¿Es posible que en virtud de la Convención de Nueva York se reconozca un laudo anulado? ¿Debería enmendarse la Convención de Nueva York para lograr una CNY 2.0? ¿Es el arbitraje de inversiones un sistema que funciona? ¿Son las críticas al arbitraje de inversiones válidas? En la presente entrevista, Gary Born responde cada una de estas interrogantes tratando muchos temas polémicos de actualidad en el arbitraje internacional.
International Arbitration under debate
Keywords: Entrevistas; https://purl.org/pe-repo/ocde/ford#5.05.00